2020
DOI: 10.3390/educsci10110327
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Personality and Academic Motivation in Education Degrees Students

Abstract: The present study aims to understand the relationship between the big five factors of personality and academic motivation. In addition, the following variables are taken into consideration; sex, age and type of educational studies. A quantitative methodology is used, in base to a not experimental, correlational study. The sample is composed of 514 students of the Faculty of Education of Leon’s University, between the three education degrees. To gather the information, participants were asked to complete the Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The findings of this study imply that students who possess strong personalities can deal with emotional, psychological and physical problems efficiently during the pandemic time, which help them to perform consistently better in their academic examinations. Further, several previous studies also show that students' personalities positively influence the students' academic performance (Yousef, 2017;Andersen et al, 2020;Fuertes et al, 2020). Further, the second hypothesis of this study confirms that those students who have higher language fluency tend to achieve more academic success regardless of the pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…The findings of this study imply that students who possess strong personalities can deal with emotional, psychological and physical problems efficiently during the pandemic time, which help them to perform consistently better in their academic examinations. Further, several previous studies also show that students' personalities positively influence the students' academic performance (Yousef, 2017;Andersen et al, 2020;Fuertes et al, 2020). Further, the second hypothesis of this study confirms that those students who have higher language fluency tend to achieve more academic success regardless of the pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…A number of studies have demonstrated a direct relationship between responsibility and intrinsic motivation (Belando et al, 2015;Menéndez and Fernández-Rio, 2017;Méndez-Giménez et al, 2018;Fernández-Espínola et al, 2020;Fuertes et al, 2020) and self-determined motivation (Merino-Barrero et al, 2019). Based on these existing studies and on our own results, it is clear that responsibility in cooperative learning techniques plays a central role in encouraging students to focus their goals on learning.…”
Section: Discussionmentioning
confidence: 99%
“…Volunteering is increasingly being associated with positive traits that help improve mental and physical health and that expand social relationships thanks to effective integration. There are authors who see volunteering as a therapeutic method of coping with feelings of depression or isolation, improving self-esteem and people’s lives by promoting emotional well-being [ 87 , 88 ]. Such situations emerged after the first wave of the coronavirus pandemic due to teleworking, which has modified activities related to face-to-face contact, as well as cognitive aspects, social well-being, and motivation, leading to the restructuring of people’s lives [ 89 ].…”
Section: Discussionmentioning
confidence: 99%